Annunciation or Adoration? The workshop practice and the hesitations of a Portuguese mannerist painter revealed by infrared reflectography - Melo, Helena P.; Cruz, António João; Valadas, Sara; Candeias, António (Springer Link, 2023)
The examination with infrared reflectography of the Annunciation and the Adoration of the Shepherds, two panels from a dismembered altarpiece attributed to the mannerist painter Francisco João (doc. 1558–1595), revealed the first documented example in Portuguese painting of the overlapping of two underdrawing layouts, each with a different subject, in a single panel painting. The paintings were examined under visible radiation and infrared reflectography was used to investigate the underdrawing in terms of the materials, graphic layout and function. Results from a previous study on the ground layers and underdrawing materials of these paintings, obtained with the analysis of micro-samples with microscopic and spectroscopic techniques, were used in the context of this research. Infrared images revealed that the underdrawing of the Annunciation mostly corresponded to the painted image but that two subjects — Annunciation and Adoration — were drawn over the prepared surface of the panel depicting the Adoration. This discovery is the first example of this procedure in Portuguese painting. The comparison with a third panel attributed to the painter, depicting another version of the Annunciation, allowed for the discussion of relevant technical procedures such as the use of cartoons, the responsibility for each main stage of painting creation and the reality of labour conditions in a regional market. The results contributed with material evidence to the scarce information of archival nature about the working methods of Portuguese mannerist painters.